Pengaruh Pengaruh insentif pajak dan literasi digital terhadap keberlangsungan UMKM berbasis green business - Reza, Fahry; Hanif Setiawan, Rifki; Bagus Pratama, Yudistira; Fauzi, Dani (Borobudur Accounting Review, 2024)
This research aims to analyze the influence of tax incentives and digital literacy on the sustainability of MSMEs with green business as a moderating variable. The ability of business actors to accelerate scientific and technological knowledge in environmentally friendly business activities is a key role in remaining afloat amidst current global competition. This research uses a quantitative approach with a survey method to collect data from various MSME actors in Pangkalpinang City. Survey respondents were limited to processing business activities and obtained 64 micro and small business actors spread across seven sub-districts in Pangkalpinang City. Through the planned behavior theory approach and using Moderated Regression Analysis (MRA), the results show that the green business variable is able to moderate the tax incentive variable and strengthen the influence on the business sustainability variable. The green business variable is also able to moderate the digital literacy variable and strengthen the influence on the business sustainability.